1994
DOI: 10.1515/bchm3.1994.375.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Fungal Metabolites and Their Biological Activities, V. Investigations Concerning the Induction of the Biosynthesis of Toxic Secondary Metabolites in Basidiomycetes

Abstract: In cultures of the basidiomycetes Heterobasidion annosum, Gloeophyllum abietinum or Armillaria ostoyae, the biosynthesis of some of their toxic secondary metabolites is enhanced up to 400-fold when they grow in the presence of an antagonist. This stimulation is induced before any cell contact occurs. The "inducing signals" are not macromolecules, polypeptides or constituents of the cell membranes, but the same toxins which are synthesized already in monocultures in very low concentrations. After excretion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 12 publications
0
45
0
1
Order By: Relevance
“…It would stand to reason then that systematic coculture screens could lead to new, perhaps cryptic, bioactive molecules that cannot be accessed otherwise. Early support for this idea came from Peipp and Sokolova (Iakovleva and Sokolova 1978;Sonnenbichler, Dietrich and Peipp 1994). Peipp, for example, found that constitutive, albeit low-level, production of a toxin by the fungus Heterobasidion annosum stimulated the biosynthesis of several toxins by a second fungus, Gloeophyllum abietinum, in liquid coculture.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…It would stand to reason then that systematic coculture screens could lead to new, perhaps cryptic, bioactive molecules that cannot be accessed otherwise. Early support for this idea came from Peipp and Sokolova (Iakovleva and Sokolova 1978;Sonnenbichler, Dietrich and Peipp 1994). Peipp, for example, found that constitutive, albeit low-level, production of a toxin by the fungus Heterobasidion annosum stimulated the biosynthesis of several toxins by a second fungus, Gloeophyllum abietinum, in liquid coculture.…”
Section: Motivationmentioning
confidence: 99%
“…Peipp, for example, found that constitutive, albeit low-level, production of a toxin by the fungus Heterobasidion annosum stimulated the biosynthesis of several toxins by a second fungus, Gloeophyllum abietinum, in liquid coculture. These overproduced toxins included oosponol (∼92-fold) and oospoglycol (∼14-fold) (Sonnenbichler, Dietrich and Peipp 1994). While numerous applications have followed, this method largely remains an underexplored strategy for the discovery of new and cryptic small molecules (Kolter and van Wezel 2016).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The process was unrelated to the presence of cell wall materials, as in fungal/plant interactions, and occurred before any cell contact had taken place (Sonnenbichler et al, 1994). For example, fomanosin and fomanoxin from Heterobasidion annosum were responseinducing metabolites.…”
Section: Control Effects By Environmental Factorsmentioning
confidence: 99%
“…Hepper (1979) observed that the spore germination and the growth of AM fungal mycelium could be stimulated or inhibited by different compounds, and the production of toxic secondary metabolites by Armillaria sp. has been reported by several authors (Peipp and Sonnenbichler, 1992;Sonnenbichler et al, 1994). The release of these compounds, induced by the presence of antagonistic fungi and plant cells, can inhibit the growth of other microorganisms and even induce cell death before any contact occurs (Peipp and Sonnenbichler, 1992).…”
Section: Discussionmentioning
confidence: 94%